Literature Review: Behavioral Counseling to Improve Students' Learning Independence - Siti Fauziah; Netrawati; Zadrian Ardi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Learning independence is the ability of students to learn independently, seeking information other than that provided by the teacher. However, many students are still found to be not independent in learning where students are still dependent on others, are not confident, have no enthusiasm and are not disciplined in learning. The behavior displayed because students are not yet independent requires the role of guidance and counseling teachers in overcoming this, namely by providing behavioral counseling. Behavioral counseling is the process of helping students solve interpersonal, emotional and decision-making problems, especially in learning independence. This counseling helps students in directing, planning, organizing and managing and controlling themselves in carrying out an activity, especially in learning, so that students can use their time as efficiently and effectively as possible. Therefore, researchers are interested in conducting a literature review on behavioristic counseling to improve learning independence in students. The literature review conducted by researchers used publications from 2019-2024 which can be accessed in full text in pdf format and scholarly (peer reviewed journals) using google schoolar in the Mendelay application, so that 7 articles were found that had been screened according to the discussion of the article raised.